The Role of Activity-Dependent DNA Demethylation in the Adult Brain and in Neurological Disorders - Bayraktar, Gonca; Kreutz, Michael R. (Frontiers in Molecular Neuroscience, 2018)
Over the last decade, an increasing number of reports underscored the importance of epigenetic regulations in brain plasticity. Epigenetic elements such as readers, writers, and erasers recognize, establish, and remove the epigenetic tags in nucleosomes, respectively. One such regulation concerns DNA-methylation and demethylation, which are highly dynamic and activity-dependent processes even in the adult neurons. It is nowadays widely believed that external stimuli control the methylation marks on the DNA and that such processes serve transcriptional regulation in neurons. In this mini-review, we cover the current knowledge on the regulatory mechanisms controlling in particular DNA demethylation as well as the possible functional consequences in health and disease.